Religion and charity : the social life of goodness in Chinese societies - Weller, Robert P. (Robert Paul), 1953- (Cambridge University Press, 2018)
This book challenges our assumptions about morality by explaining how industrialized philanthropy and universalized goodness came to dominate Chinese religious engagement.
Keywords: Religion and sociology -- China.; Charity -- Religious aspects.; Charities -- China.; Sociologie religieuse -- Chine.; Charité -- Aspect religieux.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Charities; Charity -- Religious aspects; Religion and sociology; China; Social services & welfare, criminology.; Philosophy of religion.; Christianity.; Buddhism.; Islam.; Worship, rites & ceremonies.; Charities, voluntary services & philanthropy.; Malaysia.; China.; Religion: general.; Social & cultural anthropology.; Society.